2015
DOI: 10.1093/ijnp/pyu040
|View full text |Cite
|
Sign up to set email alerts
|

BDNF-Val66Met-Polymorphism Impact on Cortical Plasticity in Schizophrenia Patients: A Proof-of-Concept Study

Abstract: Background:Brain-derived neurotrophic factor (BDNF) has been shown to be a moderator of neuroplasticity. A frequent BDNF-polymorphism (Val66Met) is associated with impairments of cortical plasticity. In patients with schizophrenia, reduced neuroplastic responses following non-invasive brain stimulation have been reported consistently. Various studies have indicated a relationship between the BDNF-Val66Met-polymorphism and motor-cortical plasticity in healthy individuals, but schizophrenia patients have yet to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 66 publications
2
19
0
1
Order By: Relevance
“…In contrast, Met carriers did not exhibit this intensity-specific effect. Given that Met carriers appear to respond more readily to atDCS than Val/Val homozygotes [( Antal et al, 2010 ; Teo et al, 2014 ; Strube et al, 2015 ) and the current data] whereas the opposite appears to be the case following rTMS or iTBS [i.e., a propensity for Val/Val homozygotes to exhibit greater cortical change than Met carriers ( Antal et al, 2010 ; Lee et al, 2013 )], our current finding and Hwang’s could be seen to be complementary. Speculatively, these findings together suggest that the genotype that predisposes a greater response to a particular NBS (rTMS for Val/Val homozygotes; tDCS for Met carriers) may also prompt a greater response to higher stimulation intensity (rTMS) or longer stimulation duration (tDCS).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…In contrast, Met carriers did not exhibit this intensity-specific effect. Given that Met carriers appear to respond more readily to atDCS than Val/Val homozygotes [( Antal et al, 2010 ; Teo et al, 2014 ; Strube et al, 2015 ) and the current data] whereas the opposite appears to be the case following rTMS or iTBS [i.e., a propensity for Val/Val homozygotes to exhibit greater cortical change than Met carriers ( Antal et al, 2010 ; Lee et al, 2013 )], our current finding and Hwang’s could be seen to be complementary. Speculatively, these findings together suggest that the genotype that predisposes a greater response to a particular NBS (rTMS for Val/Val homozygotes; tDCS for Met carriers) may also prompt a greater response to higher stimulation intensity (rTMS) or longer stimulation duration (tDCS).…”
Section: Discussionsupporting
confidence: 51%
“…In a more recent study, whereby the numbers and demographics of the BDNF Val66Met polymorphism groups were matched, Teo et al (2014) reported that Met carriers exhibited greater increases in CSE in the period 30–90 min following 9 min of 1 mA atDCS than Val/Val homozygotes. Similarly, Strube et al (2015) reported trend level increases in CSE ( p = 0.072; d = 0.799) following 13 min of 1 mA atDCS in Met carriers (8 out of a sample of 20) compared with Val/Val homozygotes. However, in older adults, the role of the BDNF Val66Met polymorphism is less well defined.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…After 20 min but not after 10 min of anodal stimulation Met allele carriers experienced enhanced corticospinal excitability compared to individuals homozygous for the Val allele (Puri et al, 2015). Furthermore, Strube et al (2015) demonstrated increased facilitatory effects of anodal stimulation on cortical plasticity in patients suffering from schizophrenia as well as in healthy controls for heterozygous compared to Val allele homozygous individuals. In contrast, cathodal stimulation caused reduced cortical inhibition in heterozygous schizophrenia patients but enhanced inhibitory effect in healthy heterozygotes indicating an interaction of interindividual differences.…”
Section: Tdcs and The Brain-derived Neurotrophic Factor (Bdnf)mentioning
confidence: 96%
“…BDNF increases neuronal dopamine content: modulates dopamine release relevant for neuronal plasticity in the ventral tegmental area (46) and also decreases dopamine in mesolimbic dopaminergic system (47). Reduction in BDNF expression was observed in the prefrontal cortex, striatum and hippocampus in animal models and patients with schizophrenia (48)(49)(50).…”
Section: The Role Of Bdnf and Cytokines In Schizophreniamentioning
confidence: 99%